2000
DOI: 10.1097/00003246-200007000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure in 100 ventilated, critically ill children: Improving the accuracy of predictive equations

Abstract: The new equations provide a more accurate alternative to current predictive methods in assessing energy requirements of ventilated, critically ill children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
4
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 20 publications
9
106
4
1
Order By: Relevance
“…In many treatment centres, Schofield prediction equations of basal metabolic rate (BMR) are used to determine the energy requirements of children pre-BMT; however, these equations are derived from indirect calorimetry methods in healthy children. 9 It has been demonstrated that these prediction equations are inaccurate in children under intensive care, 10 but it is unknown whether they can be applied to calculate energy requirements of children who will undergo a BMT. The final aim of this study was to determine if the Schofield prediction equations could accurately predict resting energy expenditure (REE) in children prior to BMT.…”
Section: Discussionmentioning
confidence: 99%
“…In many treatment centres, Schofield prediction equations of basal metabolic rate (BMR) are used to determine the energy requirements of children pre-BMT; however, these equations are derived from indirect calorimetry methods in healthy children. 9 It has been demonstrated that these prediction equations are inaccurate in children under intensive care, 10 but it is unknown whether they can be applied to calculate energy requirements of children who will undergo a BMT. The final aim of this study was to determine if the Schofield prediction equations could accurately predict resting energy expenditure (REE) in children prior to BMT.…”
Section: Discussionmentioning
confidence: 99%
“…Framson et al 17 described a heterogeneous cohort of mechanically ventilated children in whom the mean V CO 2 and V O 2 were 4.3 and 5.2 mL/kg/min, respectively, with a mean age of 5.2 y and a mean height of 102 cm. In a survey of 100 mechanically ventilated children, White et al 18 reported a mean V CO 2 and V O 2 of 5.3 and 6.3 mL/kg/min, respectively, for a cohort with a mean age of 4.5 y and a mean height of ϳ97 cm. Furthermore, in a slightly younger population with a mean age of 4.2 y, Martinez et al 19 reported a mean V CO 2 and V O 2 of 4.8 and 6.1 mL/kg/min, respectively, for a cohort of mechanically ventilated children recently admitted to the PICU.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating energy expenditure needs based on standard equations has been shown to be inaccurate and can significantly underestimate or overestimate the REE in critically ill children [13,35]. Such under/overestimates expose the critically ill child to potential underfeeding or overfeeding during the ICU stay, with significant morbidity associated with each scenario.…”
Section: Factors Affecting the Estimate Of Energy Provisionmentioning
confidence: 99%
“…The gold standard to quantify energy needs in children and in adults is the measurement of actual energy consumption by indirect calorimetry [13,35]. When large endotracheal tube leaks are present, alternative isotope methods may be used that are not affected by air leaks or the fraction of inspired oxygen (FiO 2 ) [40,41].…”
Section: Estimating Energy Needsmentioning
confidence: 99%